PERAN KESULTANAN LANGKAT DALAM PERKEMBANGAN ISLAM DI KOTA LANGKAT - Abdul Gani Jamora Nasution; Adien Inayah; Fitri Khoiroh Sayidah Harahap; Hilda Melani Purba; Nurul Handini (Universitas Maritim AMNI Semarang, 2023)
The Sultanate of Langkat is one of the richest kingdoms in East Sumatra, besides the Sultanate of Deli and the Sultanate of Serdang which have several roles. This article aims to find out the initial process of the spread of Islam in Langkat through the Langkat Sultanate, historical heritage evidence, and who are the figures who played a role in spreading Islam in Langkat. The method used is the historical research method, namely the method by reviewing the themes surrounding historical research methods in detail which is strengthened by presenting the views of historians. The findings show that in the development of Islam, the role of the Langkat sultanate included, namely, in the aspect of Education, the Langkat sultanate built several madrasas as places to study religion and figures who played a major role including Sultan Musa, Sultan Abdul Aziz, Dewa Sahdan, and others .